AN ANALYSIS OF INDONESIAN STUDENTS' PERCEPTIONS OF THE SEX RECESSION PHENOMENON IN EAST ASIA - Cindy Eka Ananda Pangestu; Arif Husnul Khuluq (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Sexual recession is a significant issue in modern life. Modern society has undergone several shifts in its perspectives on marriage. In several non-Muslim majority countries, marriage is no longer deemed appropriate for contemporary lifestyles. This study aims to investigate the phenomena of sexual recession by analyzing the perspectives of Indonesian students on marital issues in East Asia and how these issues may influence their attitudes toward marriage. It also seeks to explore the students' apprehensions over marriage. This research qualifies as descriptive qualitative research. The data was collected through interviews with 32 students, consisting of 16 women and 16 men, from various major cities on the island of Java, including Surabaya, Yogyakarta, and DKI Jakarta. The research shows that Indonesian students' perspectives on this matter are influenced by different factors such as socio-cultural aspects of East Asian society, religion, financial economics, technology, and demographics. This issue significantly influences the tendency of Indonesian students to postpone marriage. Conversely, some students remain unaffected due to their excellent perception of marriage, religious values, and Indonesian societal norms. Male students express several concerns about marriage, including financial stability, family leadership skills, and uncertainty about the future. Female students find their partner's demeanor, poor self-confidence, and acceptance of their partner's family challenging.